2021
DOI: 10.1371/journal.pntd.0009165
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in response to serological exposure markers of recent Plasmodium vivax infections in contrasting epidemiological contexts

Abstract: Background Antibody responses as serological markers of Plasmodium vivax infection have been shown to correlate with exposure, but little is known about the other factors that affect antibody responses in naturally infected people from endemic settings. To address this question, we studied IgG responses to novel serological exposure markers (SEMs) of P. vivax in three settings with different transmission intensity. Methodology We validated a panel of 34 SEMs in a Peruvian cohort with up to three years’ longi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 49 publications
3
47
1
1
Order By: Relevance
“…According to the antibody response in cohort studies, PvRBP2b (aa: 161–1454 and 1986–2653) showed the highest performance for categorizing new exposure and introduced as the top marker for detection of blood-stage P . vivax infections within the previous nine months in Thailand, Peru, and Brazil regions [ 18 ]. Furthermore, it has been shown that naturally acquired human antibodies against N-terminus of PvRBP2b can inhibit parasite invasion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the antibody response in cohort studies, PvRBP2b (aa: 161–1454 and 1986–2653) showed the highest performance for categorizing new exposure and introduced as the top marker for detection of blood-stage P . vivax infections within the previous nine months in Thailand, Peru, and Brazil regions [ 18 ]. Furthermore, it has been shown that naturally acquired human antibodies against N-terminus of PvRBP2b can inhibit parasite invasion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our analysis is that we do not account for potential variation between geographic regions and across transmission intensities, factors which are known to affect diagnostic accuracy [ 30 ]. Another limitation of this analysis is that we did not account for the effects of targeting diagnostics and treatment strategies at high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…vivax than children or newcomers) or ii) labor exposure (i.e., people in adult age increase their chances of exposure by working in forest-related jobs). Our previous work showed that antibody levels increased with the recency of infection, the number of blood-stage infections and age [ 14 ]. However, age is the stronger predictor for antibody levels in communities with high transmission level [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that antibody levels increased with the recency of infection, the number of blood-stage infections and age [ 14 ]. However, age is the stronger predictor for antibody levels in communities with high transmission level [ 14 ]. The presence of livestock in the households has been associated with low P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation